2008
DOI: 10.1002/jts.20339
|View full text |Cite
|
Sign up to set email alerts
|

Attachment organization, emotion regulation, and expectations of support in a clinical sample of women with childhood abuse histories

Abstract: Despite the consistent documentation of an association between compromised attachment and clinical disorders, there are few empirical studies exploring factors that may mediate this relationship. This study evaluated the potential roles of emotion regulation and social support expectations in linking adult attachment classification and psychiatric impairment in 109 women with a history of childhood abuse and a variety of diagnosed psychiatric disorders. Path analysis confirmed that insecure attachment was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 35 publications
6
75
0
4
Order By: Relevance
“…Consistent with these views, numerous studies have shown that childhood abuse has been associated with emotion dysregulation (e.g., Camras, Sachs-Alter, & Ribordy, 1996;Cloitre, Stovall-McClough, Zorbas, & Charuvastra, 2008;Kim & Cicchetti, 2010;Riggs, 2010;Romens & Pollak, 2012).…”
Section: Abuse Affect Regulation and Depressionmentioning
confidence: 82%
“…Consistent with these views, numerous studies have shown that childhood abuse has been associated with emotion dysregulation (e.g., Camras, Sachs-Alter, & Ribordy, 1996;Cloitre, Stovall-McClough, Zorbas, & Charuvastra, 2008;Kim & Cicchetti, 2010;Riggs, 2010;Romens & Pollak, 2012).…”
Section: Abuse Affect Regulation and Depressionmentioning
confidence: 82%
“…With repeated positive experiences, individuals internalize these emotion regulation strategies and develop confidence in the helpfulness of others. More specifically, effective adaptation in the context of secure attachment can be attributed to emotion regulation capacities, including turning to others for support when threats exceed the individual's capacity to cope alone (Cloitre et al 2008).…”
mentioning
confidence: 99%
“…Bu bulgu da, psikopatoloji ile güvensiz bağlanma arasındaki ilişkiyi araştıran pek çok çalışma ile tutarlılık göstermektedir (MacDonald ve ark. 2008;Cloitte ve ark. 2008;Venta ve ark.…”
Section: Discussionunclassified